THE USE OF ENGLISH SONGS IN IMPROVING STUDENTS' VOCABULARY MASTERY :A quasi experimental study at a second grade in one vocational school in Bandung - Febriany Eka Wati, - (2012)
This research was aimed at investigating the use of English songs in improving students' vocabulary mastery and students' response toward learning vocabulary through song. A quasi experimental design was employed with two classes consisting of 50 second graders at one of vocational schools in Bandung. The data were obtained through a pre-test, a post-test and questionnaire. The findings were analyzed statistically by using vocabulary knowledge proposed by Thornburry.The statitical computation showed that song is likely effective in improving students' vocabulary mastery (tobt 3.977 > tcrit 2.021, r = 0.497). Furthermore, song in learning activities positively promotes memorizing and gaining new vocabulary easier, developing listening skill, understanding the lesson more, and expanding knowledge. However, it is failed when students cannot identify the unknown words of the song.Teachers may utilize song in improving students' vocabulary mastery based on students' needs and language level learning objectives. The teachers can take its advantages in classroom activities to promote an effective and interesting learning atmosphere.